2006
DOI: 10.1038/sj.jhh.1002129
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of complement C3 is associated with development of hypertension: a longitudinal cohort study

Abstract: Hypertension has been associated with raised plasma levels of complement factor 3 and 4 (C3 and C4). The nature of this association is unclear. This populationbased longitudinal study explored whether C3 or C4 is associated with development of hypertension. Blood pressure and plasma levels of C3 and C4 were determined in 2178 healthy men, aged 35-50 years, initially without treatment for hypertension. Incidence of hypertension and blood pressure increase over 15.7 (72.2) years follow-up was studied in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
58
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 35 publications
6
58
1
Order By: Relevance
“…Associations implied from cross-sectional studies do not imply causation. However, the present study by Engstrom et al 27 points to a more causative role of inflammation in the development of hypertension. A reduction of blood pressure by antihypertensive agents also leads to a decrease in the levels of the inflammatory markers.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…Associations implied from cross-sectional studies do not imply causation. However, the present study by Engstrom et al 27 points to a more causative role of inflammation in the development of hypertension. A reduction of blood pressure by antihypertensive agents also leads to a decrease in the levels of the inflammatory markers.…”
contrasting
confidence: 62%
“…26 Does the complement system have a role in hypertension? In this issue of the Journal of Human Hypertension, Engstrom et al 27 studied more thanthem up for a mean of 15 years. They found that those subjects with a high baseline complement C3 levels were at a higher risk of developing hypertension in later life, which was independent of other risk factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of observational series in non-renal populations have reported positive associations between the circulating levels of components of the complement system, such as C3 and the terminal complement complex SC5b-9, and both prevalent [1,2,3,4,5] and incident [6,7,8,9,10] cardiovascular (CV) disease. Enhanced complement activation, particularly via the alternative complement activation pathway, occurs in haemodialysis (HD) patients largely as a consequence of blood-membrane interactions and is partially attenuated by the use of newer, biocompatible membranes [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In population-based studies, hypertension is usually associated with raised levels of various markers of inflammation. 1 Longitudinal studies over the last years have shown that markers of inflammation, such as white blood cells, 2 complement factor C3, 3 C-reactive protein (CRP), 4 fibrinogen 5 and a score of five acute-phase proteins, 6 are associated with incidence of hypertension or increasing blood pressure levels. These studies show that inflammation predicts the development of hypertension, and suggest that inflammation could have a function in this process.…”
mentioning
confidence: 99%